KONTRIBUSI KETERAMPILAN MEMBACA PEMAHAMAN TEKS DESKRIPSI TERHADAP KETERAMPILAN MENULIS TEKS DESKRIPSI SISWA KELAS VII SMP NEGERI 12 PADANG - Yudianda, Elvan; Hafrison, Mohd. (Universitas Negeri Padang, 2019)
ABSTRACTÂ This article reveals the contribution of skills reading comprehension text descriptions to writing skills text description grade students VII SMP Negeri Padang 12. The purpose of this research there are three. First, it describes the skills of reading comprehension text description grade VII SMP Negeri 12 field. Second, it describes the writing skills text description grade VII SMP Negeri 12 field. Third, describing the contribution of the intermediate reading comprehension text descriptions against writing skills text description grade VII SMP Negeri 12 field. This research type is quantitative descriptive method. The design used in this research is the design contribution. This research population is grade VII SMP Negeri Padang are registered on the 12th school year 2018/2019, i.e. as many as 286 students. The sample in this research are determined by proportional random sampling of 20% of the population, i.e. 54 students. Research data is a score test results intermediate reading comprehension text description and score the writing skills test result text description. The data obtained through two types of tests i.e. objective tests to measure the skills of reading comprehension text description and performance tests to measure the skills of writing a text description. The results of the research there are three. First, the skills of reading comprehension text description grade VII SMP Negeri Padang 12 are on good qualifications (B) by the value of the average 80.09. Second, the skills of writing text descriptions grade VII SMP Negeri Padang 12 are on good qualifications (B) with an average of 80.86. Third, there is a contribution of reading skills in the description of text to the skills of writing description texts of class grade VII SMP Negeri Padang 12 at 62.73%.Â Kata kunci: Kontribusi, Keterampilan, Membaca Pemahaman, Menulis, Teks Deskripsi.